How does medicine ball pull over pass and resistance band training affect passing and shooting ability? A systematic review on the sport of handball - Nida Haniyyah; Bernadeta Suhartini; Vince Louisse D. Salacup (Tanjungpura Journal of Coaching Research)
Background and Study Aim. The ability of an athlete to master passing and shooting skills is crucial for achieving success in handball. These fundamental techniques significantly influence a player's ability to contribute to their team's victory. Observations from the 2023 Pre-Province Championship revealed that poor passing and shooting skills negatively impacted gameplay, leading to unsuccessful scoring attempts and overall team performance. This study reviews literature on the effects of medicine ball pull-over pass and resistance band training on handball athletes' passing and shooting abilities.